Inhibition of the α-carbonic anhydrase from Vibrio cholerae with amides and sulfonamides incorporating imidazole moieties - Daniela De Vita; Andrea Angeli; Fabiana Pandolfi; Martina Bortolami; Roberta Costi; Roberto Di Santo; Elisabetta Suffredini; Mariangela Ceruso; Sonia Del Prete; Clemente Capasso; Luigi Scipione; Claudiu T. Supuran (Taylor & Francis Group, 2017)
We discovered novel and selective sulfonamides/amides acting as inhibitors of the α-carbonic anhydrase (CA, EC 4.2.1.1) from the pathogenic bacterium Vibrio cholerae (VchCA). This Gram-negative bacterium is the causative agent of cholera and colonises the upper small intestine where sodium bicarbonate is present at a high concentration. The secondary sulfonamides and amides investigated here were potent, low nanomolar VchCA inhibitors whereas their inhibition of the human cytosolic isoforms CA I and II was in the micromolar range or higher. The molecules represent an interesting lead for antibacterial agents with a possibly new mechanism of action, although their CA inhibition mechanism is unknown for the moment.